Prenatal sonographic diagnosis of congenital varicella syndrome - Theera Tongsong (2018)
Congenital varicella syndrome is a rare disorder occurring in less than 1% of maternal varicella during early pregnancy but is associated with high fetal morbidity and mortality. This case report aimed to describe the sonographic features of congenital varicella syndrome following maternal varicella. Well-documented maternal chicken pox was made at 12 weeks of gestation and prenatal ultrasound was performed at 16 weeks. Striking sonographic features included hydropic changes and disseminated calcifications in multiple organs, especially liver and myocardium. Elective termination of pregnancy was done at 17 weeks. The presence of disseminated calcifications could suggest the diagnosis of congenital varicella syndrome. © 2012 Wiley Periodicals, Inc.